Ancient African kingdoms A Captivating Guide to Civilizations of Ancient Africa Such as the Land of Punt, Carthage, the Kingdom of Aksum, the Mali Empire, and the Kingdom of Kush - Captivating History (New York Gareth Stevens Pub, 2011)
Describes different aspects of ancient African kingdoms, including their history, politics, religion, art, architecture, and everyday life.
Includes bibliographical references (p. 63) and index.
Keywords: Africa--History--To 1498--Juvenile literature